Radiofrequency assisted delivery of broccoli, cabbage and kale conjugated activated carbon nanoparticles for radio-photodynamic colorectal cancer vitro and vivo treatment - Samir Ali Abd El-Kaream; Yara Ahmed Mohamed Elsaid Mohamed Ahmed; Hagar Mohamed Mohamed; Amal Saleh Mohamed Soliman; Nabila Gaber Ali Hussein; Sohier Mahmoud El Kholey (Beni-Suef University Journal of Basic and Applied Sciences)
Abstract Background There is no doubt that one of the most considerable researcher dilemmas is cancer. Radiofrequency-photodynamic therapy (RFPDT) offers novel approaches to cancer treatment by combining radiofrequency-dynamic therapy and photodynamic therapy with sensitizers. While novel sensitizers for RFPDT have been synthesized successfully, their effective application is still limited. Their limited ability to transfer sensitizer's deeper intratumorally, low tumor-targeting selectivity, and failing tumor microenvironment all restrict their anti-tumor activity. The goal of the current work was to examine the most recent advancement in activated cancer treatment using radiofrequency assisted drug delivery of conjugated activated carbon nanoparticles of broccoli, cabbage, and kale (BCK-ACNP) to treat colorectal cancer (CRCA) using both in vivo and in vitro RFPDT. Materials and methods The current study included human CRCA cells (SW-620) and Swiss albino induce CRCA mice [treated with 1,2-dimethylhydrazine (DMH) and dextran sulphate sodium (DSS) only] were used in the in vitro and in vivo study. The study treatment protocol started only after CRCA induction, and involved daily administration of BCK-ACNP as RFPDT sensitizer whether or not to be exposed to laser (IRL) or radiofrequency (RF) or a combination of them for 3 min for a period of 2 weeks. Results Demonstrated that ACNP is a useful BCK delivery mechanism that targets CRCA cells directly. Furthermore, BCK-ACNP is a promising RFPS that, when used in conjunction with RFPDT, can be very effective in in vitro treating CRCA-SW-620 (in a dose-dependent manner cell viability declined, an increase in the population of cells during the S and G2/M phases indicates that the cell cycle was arrested, and an increase in the Pre-G cell population, autophagic cell death, as well as early and late apoptosis and necrosis, indicate that cell death was induced) and DMH/DSS-CRCA-induced mice in vivo (induced antiproliferative genes, p53, Bax, TNFalpha, caspase 3,9, repressed antiangiogenic and antiapoptotic genes, VEGF and Bcl2 respectively), successfully slowing the growth of tumors and even killing cancer cells, as well as lowering oxidative stress (MDA), improving the functions of the kidneys (urea, creatinine), liver (ALT, AST), and antioxidants (GPx, GR, GST, GSH, CAT, SOD, TAC). RFPDT, the photochemical or radiofrequency BCK activation mechanism, and the antioxidant capacity of non-activated BCK can all be linked to this process. Conclusion Based on the findings, BCK-ACNP shows a great promise as a cutting-edge, efficient selective delivery system for localized RFPDT-activated colorectal cancer treatment.